Indium-111 labelling of liposomal HEGF for radionuclide delivery via ultrasound-induced cavitation - Owen, J; Thomas, E; Menon, J; Gray, M; Skaripa-Koukelli, I; Gill, MR; Wallington, S; Miller, RL; Vallis, KA; Carlisle, R (Elsevier, 2019)
The purpose of this exploratory study was to investigate the combination of a radiopharmaceutical, nanoparticles and ultrasound (US) enhanced delivery to develop a clinically viable therapeutic strategy for tumours overexpressing the epidermal growth factor receptor (EGFR). Molecularly targeted radionuclides have great potential for cancer therapy but are sometimes associated with insufficient delivery resulting in sub-cytotoxic amounts of radioactivity being delivered to the tumour. Liposome formulations are currently used in the clinic to reduce the side effects and improve the pharmacokinetic profile of chemotherapeutic drugs. However, in contrast to non-radioactive agents, loading and release of radiotherapeutics from liposomes can be challenging in the clinical setting. US-activated cavitation agents such as microbubbles (MBs) have been used to release therapeutics from liposomes to enhance the distribution/delivery in a target area. In an effort to harness the benefits of these techniques, the development of a liposome loaded radiopharmaceutical construct for enhanced delivery via acoustic cavitation was studied. The liposomal formulation was loaded with peptide, human epidermal growth factor (HEGF), coupled to a chelator for subsequent radiolabelling with 111Indium ([111In]In3+), in a manner designed to be compatible with preparation in a radiopharmacy. Liposomes were efficiently radiolabelled (57%) within 1 h, with release of ~12% of the radiopeptide following a 20 s exposure to US-mediated cavitation in vitro. In clonogenic studies this level of release resulted in cytotoxicity specifically in cells over-expressing the epidermal growth factor receptor (EGFR), with over 99% reduction in colony survival compared to controls. The formulation extended the circulation time and changed the biodistribution compared to the non-liposomal radiopeptide in vivo, although interestingly the biodistribution did not resemble that of liposome constructs currently used in the clinic. Cavitation of MBs co-injected with liposomes into tumours expressing high levels of EGFR resulted in a 2-fold enhancement in tumour uptake within 20 min. However, owing to the poor vascularisation of the tumour model used the same level of uptake was achieved without US after 24 h. By combining acoustic-cavitation-sensitive liposomes with radiopharmaceuticals this research represents a new concept in achieving targeted delivery of radiopharmaceuticals.